Roles of serum fibrinogen α chain‐derived peptides in Alzheimer's disease. (5th November 2013) - Noguchi, Miwa; Sato, Toshiyuki; Nagai, Kouhei; Utagawa, Itaru; Suzuki, Itsuku; Arito, Mitsumi; Iizuka, Nobuko; Suematsu, Naoya; Okamoto, Kazuki; Kato, Tomohiro; Yamaguchi, Noboru; Kurokawa, Manae S.
<x xml:space="preserve">Abstract</x> Objective To find a blood biomarker and disease‐related peptides in Alzheimer's disease (AD), we comprehensively detected serum peptides. Methods Ion intensity of serum peptides from 62 AD patients and 82 control subjects was measured by mass spectrometry. Results A total of 157 peptides were detected from 30 AD patients and 30 healthy control (HC) subjects. Sixty out of the 157 peptide profiles discriminated between the AD and HC groups. Sixteen out of the 60 peptides were identified, 10 out of which were fragments of a fibrinogen α chain (FIBA). Among the 10 peptides, four and six peptides were derived from fibrinopeptide A (FPA, Aα1–16) and the C‐terminal region of the αC‐domain (αCDC, Aα557–610), respectively. The profile of 10 FIBA‐derived peptides combined with age discriminated between the two groups with an area under the receiver operating characteristic curve (AUROC) of 0.940. Validation of this model using a testing set of 32 AD patients and 19 HC subjects showed an AUROC of 0.717, sensitivity of 65.6%, and specificity of 73.7% by a cutoff value of 0.56420. Another value, 0.04029, showed sensitivity of 96.9%, suggesting that subjects with values less than 0.04029 rarely possess AD. FPA and αCDC showed increased ion intensity in the AD group compared with the HC group (p < 0.05). Conclusions The profile of 10 FIBA‐derived peptides combined with age would be a candidate biomarker for AD, which facilitates screening of the disease. The significant release of FPA and αCDC may be involved in the aberrant coagulation that leads to vascular damage in AD. Copyright © 2013 John Wiley & Sons, Ltd.